Collagenous sprue in a 3‐month‐old infant. Issue 1 (25th February 2015) - Jimbo, Keisuke; Aoyagi, Yo; Tanaka, Masanori; Ohbayashi, Naho; Fujii, Tohru; Kudo, Takahiro; Ohtsuka, Yoshikazu; Shimizu, Toshiaki
Abstract: Collagenous sprue (CS) is a severe malabsorption disorder, the etiology of which has not been well defined. Herein, we report the case of a 3‐month‐old infant with CS who responded to steroid and immunomodulator treatment and presented a thick subepithelial collagen band. A 3‐month‐old Japanese girl presented with severe watery diarrhea that lasted for 2 weeks. She was admitted to the referring hospital, but symptomatic improvement was not achieved with fasting and rehydration. Gastroduodenal endoscopy showed an edematous duodenal mucosal surface. Duodenal biopsy indicated severe villous atrophy with infiltration of mostly CD8‐positive T cells; and deposition of subepithelial collagen was confirmed. The subepithelial collagen deposits, however, had disappeared after treatment. Historically, child‐onset CS is extremely rare and this case is likely to be the youngest case of infantile CS. The present case suggests that CS should be considered as a differential diagnosis for intractable diarrhea, even in infants.